LAPped in Proof: LC3‐Associated Phagocytosis and the Arms Race Against Bacterial Pathogens - Grijmans, Bart J. M.; van der Kooij, Sander B.; Varela, Monica; Meijer, Annemarie H. (Frontiers in Cellular and Infection Microbiology, 2022)
Cells of the innate immune system continuously patrol the extracellular environment for potential microbial threats that are to be neutralized by phagocytosis and delivery to lysosomes. In addition, phagocytes employ autophagy as an innate immune mechanism against pathogens that succeed to escape the phagolysosomal pathway and invade the cytosol. In recent years, LC3-associated phagocytosis (LAP) has emerged as an intermediate between phagocytosis and autophagy. During LAP, phagocytes target extracellular microbes while using parts of the autophagic machinery to label the cargo-containing phagosomes for lysosomal degradation. LAP contributes greatly to host immunity against a multitude of bacterial pathogens. In the pursuit of survival, bacteria have developed elaborate strategies to disarm or circumvent the LAP process. In this review, we will outline the nature of the LAP mechanism and discuss recent insights into its interplay with bacterial pathogens.